Control de ácaros (tetranychus urticae), en tres variedades de rosas (rosa sp), para exportación. - Bastidas Muñoz, Marco Tulio (2024)
The phytophagous mite Tetranychus urticae is considered the main pest in rose cultivation. This, added to the indiscriminate use of chemical pesticides, has caused this pathogen to generate resistance. Therefore, the need to look for new environmentally friendly control alternatives is created. Hence, in the present study it is externalized as an organic alternative to the use of Phytolacca bogotensis K extract, because it has a large amount of saponins; They can act by contact or ingestion by breaking the surface tension and forming complexes with sterols in the permeable cell membrane and can be considered as a mite controller. That is why, in the present investigation, the effectiveness of the Phytolacca bogotensis K extract was analyzed at two doses (30 cc/l and 40 cc/l), in relation to the commercial chemical control Trisiloxane (0.5 cc/l); This was carried out in the facilities of the Fresh Market commercial farm, which is located in the Cayambe canton, province of Pichincha, where their effectiveness was analyzed in relation to three varieties of roses such as: Freedom, High Exotic and Jessica; The experimental design used in this research was a 3 x 3 factorial arrangement implemented in a randomized complete block design; The duration of the experiment was 16 days, where the interaction of the extract with the mite Tetranychus urticae in its nymph and adult phases was observed. The results obtained in relation to the effectiveness of the treatments to control red spider, first presented Trisiloxane 0.5 cc/l, followed by P. bogotensis extract at 40 cc/l, as the best alternative treatment to apply in the nymph and adult stages with an effectiveness greater than 93%. On the other hand, of the varieties analyzed, it can be mentioned that the Freedom variety was the one that presented the lowest incidence with respect to the degree of infestation of the pest. Therefore, apply P. bogotensis extract to control mites and thus favor the reduction of active ingredient/ha/year in the productive agro-ecosystem of these cultivars or when a plant health situation warrants.